2022
DOI: 10.3233/jvr-211169
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to work-based learning experiences: A mixed methods study of perceptions from the field

Abstract: BACKGROUND: Work-based learning experiences (WBLEs) are significantly associated with improved postschool employment outcomes for students with disabilities; however, little is known about the specific barriers affecting implementation of WBLEs. OBJECTIVE: The purpose of this study was to identify community-and school-related barriers to implementing WBLEs. METHODS: This study used a mixed methods approach to analyze survey data from 170 secondary transition staff providing WBLEs to students with disabilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Participants described challenges related to (a) establishing and sustaining appropriate WBLEs, (b) securing high-quality staff, (c) gaining support from important partners, and (d) navigating logistics. Several findings from this study align with previous research that has identified staffing, transportation, scheduling, and limited availability of appropriate WBLEs as challenges to providing WBLEs for students with disabilities (Awsumb et al, 2022; Bromley et al, 2022; Collet-Klingenberg & Kolb, 2011 ; Kim & Dymond, 2010; Pickens & Dymond, 2015; Rooney-Kron & Dymond, 2021). Taken together, these findings indicate that inadequate resources and logistical concerns persist regardless of a student’s disability category or support needs.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Participants described challenges related to (a) establishing and sustaining appropriate WBLEs, (b) securing high-quality staff, (c) gaining support from important partners, and (d) navigating logistics. Several findings from this study align with previous research that has identified staffing, transportation, scheduling, and limited availability of appropriate WBLEs as challenges to providing WBLEs for students with disabilities (Awsumb et al, 2022; Bromley et al, 2022; Collet-Klingenberg & Kolb, 2011 ; Kim & Dymond, 2010; Pickens & Dymond, 2015; Rooney-Kron & Dymond, 2021). Taken together, these findings indicate that inadequate resources and logistical concerns persist regardless of a student’s disability category or support needs.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, findings from this study shed additional light on the unique challenges to gaining support from important partners (e.g., administrators, employers) when providing WBLEs for students with ESN. Only one other study identified a lack of administrator support as a primary concern when providing WBLEs for students with ID (see Rooney-Kron & Dymond, 2021); teachers in other studies rated administrator support as a moderate-to-low-level barrier in terms of its impact on their provision of WBLEs (see Bromley et al, 2022; Kim & Dymond, 2010). A lack of administrator support reported by teachers in the current study draws attention to the unique needs of students in this population and raises questions about administrators’ capacity to provide adequate support for teachers who serve students with ESN.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations